2013
DOI: 10.1097/mpa.0b013e3182968e00
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Metabolism/Antioxidant Genes May Mediate the Effect of Dietary Intake on Pancreatic Cancer Risk

Abstract: Objectives A source of variation for inconsistent dietary-pancreatic cancer associations may be individuals carrying constitutional metabolism/antioxidant gene variants differentially benefit compared to homozygous individuals. Seventy-six tag SNPs were genotyped in thirteen candidate genes to test differential associations with pancreatic adenocarcinoma. Methods A clinic-based case-control design was used to rapidly ascertain 251 cases and 970 frequency matched controls who provided blood samples and comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 85 publications
1
8
0
Order By: Relevance
“…Genetic variations in the CAT enzyme may modulate disease risk. 11 Several studies have suggested that CAT polymorphisms might be associated with a risk of various cancers such as breast cancer, 20 cervical cancer, 21 prostate cancer, 22 pancreatic cancer, 23 and colorectal cancer. 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic variations in the CAT enzyme may modulate disease risk. 11 Several studies have suggested that CAT polymorphisms might be associated with a risk of various cancers such as breast cancer, 20 cervical cancer, 21 prostate cancer, 22 pancreatic cancer, 23 and colorectal cancer. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Several research have investigated the association between the CAT SNPs rs1001179, rs769217, and rs7943316 polymorphisms and the risk of various cancers such as breast cancer, 20 cervical cancer, 21 prostate cancer, 22 pancreatic cancer, 23 and colorectal cancer 24 in various races. Three studies to date have examined the influence of CAT polymorphism on the risk of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…European Project, Alexander, under the Seventh European Community Framework Programme (Grant Agreement Number 280761) 53.9 c, 4, α (K. Ikeda & Kusano, 1983) Oberg, et al, 2011;Jansen, Robinson, Stolzenberg-Solomon, Bamlet, Tan, Cunningham, et al, 2013) Case-control study with 532 cases of pancreatic cancer Adjusted OR of 0.60 (0.31-1.2) for ≥2 servings of whole grains/day versus 1 for <1 serving/day Frequency of consumption of brown rice and tortillas was negatively associated with OR while frequency of (Chan, Wang, & Holly, 2007) oatmeal/oat bran were positively associated with OR. Case-control study with 186 cases of pancreatic cancer Adjusted OR of 0.52 (0.21-1.30) for highest quartile of fibre intake versus 1 for lowest No significant trend also noted for association of frequency of fruit and vegetable consumption and OR (J.…”
Section: Discussionmentioning
confidence: 99%
“…The group of increasing risk changes includes catalase ( CAT ) and GSTP1 , while to those with reducing character belongs glucosidase alpha acid ( GAA ), UGT2B4 (UDP-glucuronosyltransferase 2 family, polypeptideB4) and MT1E (metallothionein 1E) 48.…”
Section: Nuclear Dna Changesmentioning
confidence: 99%